Efficacy of locally-available cleaning methods and household chlorination at inhibiting biofilm development in jerricans used to store household drinking water. Issue 2 (17th December 2020) - String, Gabrielle M.; Domini, Marta; Badr, Hanaa; Brodsky, Hannah; Kamal, Yarmina; Tatro, Tyler; Johnston, Miranda; Ogudipe, Anthonia; Vu, Trang Nha; Wolfe, Marlene K.; Lantagne, Daniele S.
Abstract : Jerricans, commonly used to store household drinking water, are challenging to clean and biofilms may develop inside containers storing contaminated water. A large-scale laboratory experiment was conducted to test methods to inhibit biofilm growth. Abstract : Jerricans are commonly used to store household drinking water. However, biofilms can grow on jerrican surfaces and contaminate water. To investigate mechanisms to inhibit biofilm growth, 72 5 L jerricans containing E. coli -spiked water were incubated for 10 weeks in the laboratory. Jerricans were stratified by: water treatment with chlorine; turbidity; and, regular cleaning with NaOCl, rocks, sand, NaOCl/rocks, and NaOCl/sand. At study end, surface E. coli was enumerated and biofilms imaged using epifluorescence microscopy; free chlorine residual was tested regularly. We found biofilms grew rapidly in jerricans (presence confirmed in 3 weeks), and chlorine demand within jerricans increased over time as FCR decreased from 1.16 to 0.59 mg L −1 over the course of the study in 5 NTU treated waters. Biofilm growth was significantly inhibited by water treatment with chlorine ( p = 0.03), and was inhibited by cleaning with NaOCl or NaOCl/rocks. Cleaning with rocks increased surface roughness, which promotes biofilm growth. These results highlight the need for research on locally-appropriate cleaning methods and/or alternatives ( e.g. replacement, biofilm-resistant surfaces) to ensure jerricans provide safe storage of drinking water.